Direct Laser Annealing of Surface‐Enhanced Raman Scattering Substrates. Issue 12 (17th October 2019) - Cao, Bolun; Mu, Yunyun; Zhang, Xinping
Abstract : A laser‐annealing technique for the fabrication of surface‐enhanced Raman scattering (SERS) substrates consisting of closely packed gold nanoparticles (AuNPs) with high densities and small separation distances is reported. Laser annealing enables strongly localized interaction between the laser spot and the colloidal AuNPs within the irradiation area. Multiple stages of the alternative spin‐coating of colloidal AuNPs and laser‐annealing processes enable filling of the gaps between the AuNPs by newly produced ones in the subsequent stages. Thus, both the fill factor and the distribution density of the AuNPs are increased largely with increasing the number of fabrication stages, which favors the improvement of the SERS performance. In contrast, the conventional furnace or hot‐plate annealing heats the substrate and the colloidal film simultaneously, and the melted AuNPs tend to aggregate to form larger ones with large separation distance. Thus, compared with the SERS effective by furnace‐annealed substrates, laser‐annealed substrates supply a further enhancement factor larger than 3.7. Thus, laser annealing is proved as a more effective approach for the fabrication of SERS substrates through annealing colloidal AuNPs. Abstract : Direct laser annealing of colloidal gold nanoparticles (AuNPs) using a green laser produces closely packed gold nanoisland structures with high density. Different from hot‐plate or furnace annealing, laser annealing only allows short‐range aggregation of molten AuNPs without heating the substrate. Small gap width between the closely arranged gold nanoislands enables the construction of high‐density hot spots and much surface‐enhanced Raman scattering (SERS) signals.